Bifosfonates to Osteogenesis imperfect - Camilo Garcés-Constain; E. Beltrán-Zúñiga; Maria Amparo Acosta-Aragón (Revista de la Facultad de Ciencias de la Salud, 2012)
Background: Osteogenesis imperfect is a disease of genetic origin, which causes a defect in the formation of collagen type I, with the common feature of presenting congenital bone fragility and heterogeneous clinical manifestations that can range from a small number of fractures or osteopenia, to severe skeletal deformities with fatal results. It’s incidence is variable and there is no clear data in Colombia, equally affects all ethnicities and genders, with primary commitment to the long bones of the limbs, and sequels such as deformities, bone pain and functional limitation unwieldy for everyday activities, the personal and social development. It is classified into nine major subtypes according to the genetic, radiological and clinical characteristics, the last ones being the most important to discriminate between mild, moderate or severe and lethal disease, and determining prognosis and therapeutic interventions. Objective: Describe the current concepts of etiology, pathophysiology, emphasizing on therapeutic measures. Conclusions: It needs an interdisciplinary approach, which has been limited to conservative and surgical correction of deformities, without touching the intrinsic fragility of the disease. Bisphosphonates are effectives. It improves the quality of life and chances of surgical correction. Zoledronic acid is the most effective.